Defense Mechanisms of Gingiva (Journal of Orofacial Research, 1970)
Defense is resisting an attack; there are numerous protective mechanisms that work in the oral cavity against various insults. Gingiva is constantly subjected to a wide array of mechanical, chemical and antigenic challenges — some of which are transient and others permanent. This review will discuss how the gingiva prepares and safeguards itself via diverse defense mechanisms in the face of this challenging environment.